Um sistema para monitorar e controlar a qualidade de processos - Sena Junior, Marcelino Pereira de (Brasil, 2021)
The competitor in the current market has caused companies to always seek higher levels of quality in their processes, whether they are products or services. One way to maintain the quality of such processes is the quality tools that help companies maintain their quality standards, one of which is Statistical Process Control (CEP). CEP is a continuous monitoring of a flow of activities, in which adjustments can be made, so that the result of the process is in accordance with a defined standard. However, performing CEP calculations manually to be laborious in very large production scales, as well as proprietary software can present a high cost for a small business owner. Thus, this work aims to build a software system that meets your needs and also be a tool that can help in the teaching of learning of Production Engineers. The project methodology is qualitative and exploratory. Exploratory, as the construction of a software will be carried out, this includes the bibliographical study, the gathering of requirements through declaration, the definition of documents, as well as their implementation. Qualitative, by an evaluation of the software's functions. As a result, the system modeling with Use Case and Class diagrams is presented, as well as the logical database design and the set of prototypes of system screens. Then, an initial study with the first proposal developed. Finally, a proof of concept with the final software developed.